2022
DOI: 10.3389/fpls.2022.878558
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping and Cloning of a Major QTL qph12, Which Simultaneously Affects the Plant Height, Panicle Length, Spikelet Number and Yield in Rice (Oryza sativa L.)

Abstract: Plant height is one of the most important agronomical traits in rice (Oryza sativa L.). Introducing the semidwarf rice in the 1960s significantly enhanced the rice yield potential in Asia. Implementing near-isogenic lines (NILs) is the most powerful tool for the identification and fine mapping of quantitative trait loci (QTLs). In this study, 176 NILs were produced from the crossing and back-crossing of two rice cultivars. Specifically, the indica rice cultivar Jiafuzhan served as a recipient, and the restorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The genetic background of NIL128 homozygous material was analysed using 296 primers that showed polymorphism between Hui1586 and Jiafuzhan cultivars [ 20 ]. The results showed that five markers exhibited homozygous alleles of Hui 1586, including Ind1-3 on chromosome 1, RM7286 on chromosome 2, Ind3-18 on chromosome 3, RM566 on chromosome 9, and RM19 on chromosome 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic background of NIL128 homozygous material was analysed using 296 primers that showed polymorphism between Hui1586 and Jiafuzhan cultivars [ 20 ]. The results showed that five markers exhibited homozygous alleles of Hui 1586, including Ind1-3 on chromosome 1, RM7286 on chromosome 2, Ind3-18 on chromosome 3, RM566 on chromosome 9, and RM19 on chromosome 12.…”
Section: Resultsmentioning
confidence: 99%
“…The indica rice cultivar Jiafuzhan and the japonica rice cultivar Hui1586 were preserved at the Rice Research Institute, Fujian Academy of Agricultural Sciences, China. In the early stage, 176 NILs were constructed with the indica cultivar Jiafuzhan as the acceptor and the japonica cultivar Hui1586 as the donor [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, validation of these identified and stable or previously reported QTLs in different genetic backgrounds is challenging, and very limited efforts have been made toward it. Several stable yield QTLs and genes have been identified and cloned in other crop species, such as rice ( Xing and Zhang, 2010 ; He et al., 2022 ). However, progress toward functional characterization of seed yield-related QTLs or genes is lagging in soybean.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…With the continuous advancement of research techniques and the utilization of new research materials, several new PH-related genes are being localized and cloned. For example, a PH major quantitative trait locus (QTL), qph12, was identified in rice, and knockout experiments verified that LOC_Os12g40490 is the key candidate gene, which is an auxin-responsive Aux/IAA gene family member (He et al, 2022). SD8 (LOC_Os08g45030), a PH-related IAA-associated gene, was also identified, which encodes an ATP-binding cassette-B (ABCB) transporter, and the mutant lines were able to reduce PH and adjust the flag leaf angle, thereby optimizing rice structure without affecting yield (Qu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%